2021
DOI: 10.17478/jegys.988313
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Challenges In The Senior Phase Natural Sciences Classroom in South African schools

Abstract: This paper investigated some of the teaching challenges Senior Phase Natural Sciences teachers' experiences during their classroom practices in some of the rural schools positioned in the Vhembe District, Limpopo Province of South Africa. It was an interpretative qualitative study wherein two Senior Phase Natural Sciences teachers participated in the study. The data of the study was obtained through individual interviews with teachers as well as lesson observations. The findings show numerous challenges in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Teaching in rural schools is characterised by a lack of basic teaching and learning resources, as well as other resources such as computers, internet access, and funding (National Education Infrastructure Management System [NEIMS], 2020; Shikalepo, 2020). Rural schools face numerous limitations in resources to support teaching and learning, including a shortage of textbooks, laboratory facilities and equipment, ICT resources, and inadequate infrastructure (Netshivhumbe & Mudau, 2021). Research shows that this lack of resources creates obstacles for students in rural schools, resulting in discouragement, failure, and higher dropout rates (Abotsi et al, 2018).…”
Section: Affiliationsmentioning
confidence: 99%
“…Teaching in rural schools is characterised by a lack of basic teaching and learning resources, as well as other resources such as computers, internet access, and funding (National Education Infrastructure Management System [NEIMS], 2020; Shikalepo, 2020). Rural schools face numerous limitations in resources to support teaching and learning, including a shortage of textbooks, laboratory facilities and equipment, ICT resources, and inadequate infrastructure (Netshivhumbe & Mudau, 2021). Research shows that this lack of resources creates obstacles for students in rural schools, resulting in discouragement, failure, and higher dropout rates (Abotsi et al, 2018).…”
Section: Affiliationsmentioning
confidence: 99%
“…The integration of Pedagogical Content knowledge (PCK) and Content Knowledge (CK) is an indication of how knowledgeable teachers are about the content they are teaching and how to teach it, and the lack thereof contributes to teaching difficulties (Kleickmann, et al, 2012). Mudau and Nkopodi (2015) found that the less content knowledge a teacher has, the less confidence they have in teaching science which makes it a challenge to teach science.…”
Section: Content Knowledgementioning
confidence: 99%
“…When attempting to understand the applications of the theoretical framework in answering the research question, the links between the various themes must be understood. When content knowledge is poor, a teacher may have difficulty teaching the topic (Mudau et al, 2015), rely more on textbooks (Chavan, 2016), or include fewer scientific investigations due to lack of confidence (Edessa, 2017).…”
Section: Teacher Understanding Of Learnersmentioning
confidence: 99%
“…The periodic table is a central concept and/or a system in chemistry teaching as it provides a framework for organizing and understanding the properties and behaviour of matter at the elemental and atomic levels (Scerri, 2019; Cao, Vernon, Schwarz, & Li, 2021). However, despite its importance, the periodic table remains a challenging topic for many learners to comprehend and often requires hours of memorization without fostering deep conceptual understanding (Mudau, & Nkopodi, 2015;Traver et al, 2021;Mhlongo & Sedumedi, 2023). In an attempt to address this challenge, the researchers have thought of a range of innovative teaching approaches that would enhance learners' engagement and conceptual understanding of abstract Chemistry concepts through the understanding of the periodic table.…”
Section: Introductionmentioning
confidence: 99%